Upaya Peningkatan Pembelajaran Berbasis Zakat, Sedekah, dan Infaq Untuk Optimalisasi Aspek Moral, Emosional dan Sosial Terhadap Siswa SDN 105337 Pantai Labu - Alwi Dani Rizki Simbolon; Nurman Ginting (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2024)
Learning based on Zakat, Sedekah, and Infaq (ZIS) plays a significant role in shaping students' character, particularly in moral, emotional, and social aspects. This study aims to identify efforts to enhance ZIS learning that can be implemented at SDN 105337 Pantai Labu. The research employs a qualitative approach with interview, observation, and documentation techniques. The results reveal that the implementation of ZIS-based learning not only improves students' understanding of Islamic finance concepts but also positively impacts the development of moral character, such as empathy, social awareness, and collaboration skills. Furthermore, students involved in the ZIS program demonstrate improvements in emotional aspects, including emotional management and self-confidence. This study recommends the integration of ZIS learning into the school curriculum to foster a more caring and responsible generation.